The Impact of Ecoport Socialization and Port Waste Management System on Greenport Implementation - Tri Joko Waluyo; Rizal Rochmansyah; Pesta Veri Ahmadi Napitupulu (Meteor STIP Marunda, 2024)
Port Waste Management System (PWMS) is a comprehensive waste management approach employed at ports to mitigate environmental harm. PWMS encompasses the collection, segregation, and disposal of various types of waste generated at ports, including solid, liquid, and hazardous waste. Through the adoption of sustainable technologies such as renewable energy and efficient water management, ports can significantly reduce their carbon footprint and ecological impact. Ecoport and Port Waste Management System advocate for sustainable practices within port operations. This study aims to assess the influence of the Ecoport Socialization Program on Greenport implementation at Tanjung Priok Port, aiming to enhance awareness regarding the importance of minimizing environmental impact and improving resource efficiency within the port sector. The findings indicate a positive and statistically significant relationship between the Port Waste Management System (X2) and Greenport Implementation (Y), with a coefficient value (Original Sample column) of 0.579 and P-Values of 0.000 < 0.05. Furthermore, the Q-Square (Q2) value for Greenport Implementation (Y) is 0.465, indicating that Ecoport Socialization (X1) and Port Waste Management System (X2) possess predictive relevance for Greenport Implementation (Y). Combined, Ecoport Socialization (X1) and Port Waste Management System (X2) account for 59.6% of the variance in Greenport Implementation (Y), with the remaining 40.4% attributable to other factors. In conclusion, this study demonstrates that Ecoport socialization and Port Waste Management System significantly contribute to explaining Greenport Implementation.